Engineering Silicon Oxide by Argon Ion Implantation for High Performance Resistance Switching - Zhao, L.; Ng, W. H.; Knights, A. P.; Stevanovic, D. V.; Mannion, D. J.; Mehonic, A.; Kenyon, A. J. (Frontiers in Materials, 2022)
We report that implanting argon ions into a film of uniform atomic layer deposition (ALD)-grown SiOx enables electroforming and switching within films that previously failed to electroform at voltages <15V. We note an implantation dose dependence of electroforming success rate: electroforming can be eliminated when the dosage is high enough. Our devices are capable of multi-level switching during both set and reset operations, and multiple resistance states can be retained for more than 30000 seconds under ambient conditions. High endurance of more than 7 million (7.9×10^6) cycles is achieved alongside low switching voltages (±1V). Comparing SiOx fabricated by this approach with sputtered SiOx we find similar conduction mechanisms between the two materials. Our results show that intrinsic SiOx switching can be achieved with defects created solely by argon bombardment; in contrast to defects generated during deposition, implantation generated defects are potentially more controllable. In the future, noble ion implantation into silicon oxide may allow optimization of already excellent resistance switching devices.